2021
DOI: 10.1186/s12974-021-02250-8
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ improves cognitive function and reduces neuroinflammation by ameliorating mitochondrial damage and decreasing ROS production in chronic cerebral hypoperfusion models through Sirt1/PGC-1α pathway

Abstract: Background Microglial-mediated neuroinflammation plays an important role in vascular dementia, and modulating neuroinflammation has emerged as a promising treatment target. Nicotinamide adenine dinucleotide (NAD+) shows anti-inflammatory and anti-oxidant effects in many neurodegenerative disease models, but its role in the chronic cerebral hypoperfusion (CCH) is still unclear. Methods The bilateral common carotid artery occlusion (BCCAO) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 70 publications
4
84
0
Order By: Relevance
“…It can reduce neuronal loss, suppress inflammation, and inhibit apoptosis and oxidative stress in the hippocampus of VaD rats [ 46 48 ]. Previous studies have shown that chronic cerebral hypoperfusion leads to a downregulation of SIRT1 in the brain of VaD rats, which is similar to our study [ 15 , 47 ]. However, oral administration of LIG enhanced the expression of SIRT1 in the cortex and the hippocampus of VaD rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can reduce neuronal loss, suppress inflammation, and inhibit apoptosis and oxidative stress in the hippocampus of VaD rats [ 46 48 ]. Previous studies have shown that chronic cerebral hypoperfusion leads to a downregulation of SIRT1 in the brain of VaD rats, which is similar to our study [ 15 , 47 ]. However, oral administration of LIG enhanced the expression of SIRT1 in the cortex and the hippocampus of VaD rats.…”
Section: Discussionsupporting
confidence: 92%
“…Sirtuin1 (SIRT1), a NAD+-dependent deacetylase, is thought to participate in the regulation of cellular senescence and aging [ 12 ]. Some studies have shown that increasing the expression of SIRT1 could improve cognitive impairment in VaD rats by promoting angiogenesis, anti-inflammatory, antioxidant, and antiapoptosis [ 13 15 ]. Interestingly, recent studies have reported that the activation of SIRT1 could alleviate cell damage caused by ER stress [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased PGC-1α expression was shown to reduce NLRP3 inflammasome activation, proinflammatory cytokine production, and decrease neuroinflammation and depression-like behavior [ 239 , 240 ]. Several compounds have been identified in other models of neurological damage that reduce neuroinflammation and oxidative damage through AMPK/PGC-1α– or SIRT1/PGC-1α–mediated pathways and improve cognitive outcomes [ 241 , 242 , 243 , 244 ]. Melatonin is a hormone involved in control of the sleep–wake cycle and has anti-inflammatory, anti-oxidative, and mitochondrial protective properties.…”
Section: Covid-19 and Neurodegenerationmentioning
confidence: 99%
“…In a rat model of chronic cerebral hypoperfusion (a major cause of vascular dementia), direct supplementation with NAD + (intraperitoneal injection of 250 mg/kg/day for 8 weeks) significantly ameliorated the impairment of learning and memory [ 11 ]. In another study, the cognitive impairment caused by chronic cerebral hypoperfusion was shown to be improved in mice by treatment with NAM (intraperitoneal injection of 200 mg/kg/day for 30 days), with significant benefits to learning, memory, anxiety, and depression-like behaviours [ 23 ].…”
Section: Dementiamentioning
confidence: 99%
“…Additionally, it is a key substrate for ADP-ribosylation by poly-ADP-ribose polymerase (PARP) enzymes, protein deacetylation by sirtuins, and cyclic ADP-ribose (cADPR) production by CD38 and CD157 [ 5 ]. Numerous mechanisms have been proposed to explain how supplementation in support of NAD + levels can achieve neuroprotection, with evidence from different contexts supporting reduced oxidative stress [ 6 ], lowered protein aggregation [ 7 ], anti-inflammatory effects [ 8 ], the stimulation of neuroprotective HCA2 macrophages [ 9 ], the blocking of autophagy [ 10 ], and the amelioration of mitochondrial damage and dysfunction [ 11 ]. This evidence leads to the conclusion that the relevant pathway is complex and likely multifactorial.…”
Section: Introductionmentioning
confidence: 99%